DESIGNING ENERGY EFFICIENCY GLAZED STRUCTURES WITH COMFORTABLE MICROCLIMATE IN NORTHERN REGION - Pukhkal, Viktor; Bieliatynskyi, Andrii; Murgul, Vera (Journal of Applied Engineering Science, 2016)
With the rising demand for entirely glass facades and glass roofs, the need to carry out an additional analysis of conditions to secure comfortable microclimate has appeared. There is a peculiar issue to work out design principles of glass buildings in the northern regions. The article deals with the general data of inside temperature in rooms and on internal glass surface of commercial pavilions made of glass. The data to work out the design of glazing for considerable areas of glass facades and glass roofs in the northern regions have been given herein. The factors, which make it uncomfortable for people to stay inside glass space, have been researched. Heat losses in commercial pavilions with various dimension ratios and the amount of energy consumed for heating have been determined in the case of the weather conditions in the northern city of Saint-Petersburg (Russia).